TAGMEMICS (An Introduction to Tagmemics Concepts) - Abd. Muqit (IAIN MADURA, 2012)
The tagmemics is a unit comprising a function and a class of items fulfilling that function. It is most suitable in describing languages and applied to the description of a very large number of hitherto unrecorded languages. Tagmemics differs from alternative systems of grammatical analysis in that it defines the basic units of language (tagmemes) as composite elements, one part being the “slot,” or “function,” and the other the “filler,” or “class.” One such tagmeme, at the syntactic level of analysis, might be the noun-as-subject (in which the noun is a class that “fills” the subject “slot” in a construction). This article also introduce how tagmemics show for a syntactical counterpart to the phonological and morphological terms, phoneme and morpheme–something at the sentence level which could function as a key identifying unit in the same way that these well- established terms functioned